2017
DOI: 10.1038/mi.2016.107
|View full text |Cite
|
Sign up to set email alerts
|

IL-36 receptor deletion attenuates lung injury and decreases mortality in murine influenza pneumonia

Abstract: Influenza virus causes a respiratory disease in human that can progress to lung injury with fatal outcome. The interleukin (IL)-36 cytokines are newly described IL-1 family cytokines that promote inflammatory responses via binding to the IL-36 receptor (IL-36R). The mechanism of expression and the role of IL-36 cytokines is poorly understood. Here, we investigated the role of IL-36 cytokines in modulating the innate inflammatory response during influenza virus-induced pneumonia in mice. The intranasal administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 51 publications
6
73
0
1
Order By: Relevance
“…Signaling by IL-36γ and IL-36R has previously been shown to increase chemokine levels and promote leukocyte recruitment in both the skin and lungs [14, 6264]. Indeed, we observed that IL-36γ exposure elicited significantly increased levels of the chemokines CCL20 and KC measured in both FRT tissue and vaginal lavages 4h following treatment (Fig.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Signaling by IL-36γ and IL-36R has previously been shown to increase chemokine levels and promote leukocyte recruitment in both the skin and lungs [14, 6264]. Indeed, we observed that IL-36γ exposure elicited significantly increased levels of the chemokines CCL20 and KC measured in both FRT tissue and vaginal lavages 4h following treatment (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…IL-36α, - β, and -γ are all expressed in nonhematopoietic cells, including keratinocytes and mucosal epithelial cells, but are induced in response to different inflammatory stimuli [23]. For example, IL-36α and IL-36γ have been shown to be robustly induced in bronchial epithelial cells in response to microbial products, bacterial infection, and viral infection, suggesting that the IL-36 cytokines may play an important role in epithelial host defense [14, 18, 19, 24, 25]. Indeed, IL-36γ −/− mice exhibited delayed clearance of Streptococcus pneumoniae and Klebsiella pneumoniae in lung infections, decreased Th1 and Th17 cytokine levels, and increased mortality [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of antimicrobial peptides provides additional means to inhibit viral replication and modulate antiviral immune responses, for example, by triggering virus aggregation or trapping, viral envelope disruption, and enhanced IFN-b production (118,119). In agreement with this, an in vivo role for IL-36a was demonstrated in a murine model of influenza pneumonia (120). However, given the apparent redundancy in how the IL-1s and IL-36s activate cells ( Fig.…”
Section: Role In Immunity Against Virusesmentioning
confidence: 58%
“…Hence, in combination with IL-1a, the IL-36s may promote immunity against these pathogens to clear or control the infections over time. Although this review is focused on skin immunity, it is noteworthy and in agreement with this hypothesis that IL-36a plays an essential role in initiating immune responses against influenza (120). The influenza protein NS1 (nonstructural protein 1) blocks NLRP3 function (134,135), similar to inflammasome inhibition by other viruses, as described above.…”
Section: Viral Immune Evasion and Potential Counteraction By Il-36mentioning
confidence: 91%